A study on the Social Representations of pre-operative patients on bariatric surgery (Research, Society and Development, 2022)
Obesity is a disease that affects millions of people around the world and, due to its specificities, the subjects affected by it share the feeling of belonging to the same social community. Even in the face of several possible treatments, bariatric surgery has great adherence by the Brazilian community. In this sense, the present manuscript analyzed the possible Social Representations shared between 16 patients in the preoperative stage of By-pass surgery, resulting from their knowledge about the inducing theme "bariatric surgery". The data were constituted through the technique of Evocation Free of Words and analyzed through the structuralist approach, which made possible the construction of the four-house frame of social representations.According to the results, it was possible to identify that the semantic groups that configure the central nucleus of this representation are concepts related to 'Health , 'Physical changes' and 'Well-being' In addition, the present study elucidates that few patients are concerned about the importance of eating well and with the other necessary care in the pre, trans and postoperative periods.